Inverter Open-circuit Fault Diagnosis and Its Fault-tolerant Method Based on Three-phase Current Detection - WANG Zhi-yuan; ZHANG Jie; WANG Yu-qi; SONG Wen-sheng; GE Xing-lai (机车电传动)
Inverter open-circuit fault diagnosis and fault-tolerant method based on vector-controlled induction machine drive system with utilization of remained bridges was proposed. Signals of inverter three-phase current were taken as characteristic parameter, and based on wavelet principle, eigenvectors were extracted, and then inverter failure was detected through the support vector machine (SVM). When inverter fault was detected by SVM, traditional six-switch topology was changed to newly four-switch topology with four-switch mode algorithm modulation of space vector pulse width modulation (SVPWM). Validity and effectiveness of the SVM for inventor open-circuit fault diagnosis and the control strategy for four-switch inverter was proved by simulation.